Critical Discourse Analysis of Comments on CNN's Instagram Post about Donald Trump's Meeting with Volodymyr Zelensky - Rizma Aidha Nur Khasanah; Malikatul Laila; M Mujazin (Universitas Muhammadiyah Surakarta, 2025)
Purpose: (1) To identify the ideologies of users as reflected in comments on CNN News Instagram posts about the meeting between Donald Trump, JD Vance, and Volodymyr Zelensky, (2) to examine how Instagram functions as a social media platform in shaping public discourse about the Trump–Zelensky meeting.Methodology: descriptive qualitative with Teun A van Dijk's critical discourse analysis (CDA) approach, which covers three dimensions, namely macrostructure, superstructure, and microstructure. A total of 160 clean comments were collected through purposive sampling. These comments were selected based on the completeness of the arguments, the use of evaluative language, the clarity of the theme, and their suitability for CDA analysis. Four selected comments were analyzed in depth. Teun A van Dijk's (1998) socio-cognitive approach is used to understand Instagram's role in the process of shaping public discourse.Results: Four main ideologies were found in the Instagram comments: anti-US power rejection ideology, diplomatic ethics, anti-Zelensky nationalism and populism, and pro-peace. In the socio-cognitive analysis, Instagram acts as an active and persuasive space for discourse production, a place for ideological reproduction and negotiation, and algorithmic visibility to reinforce the dominance of certain ideologies.Applications/Originality/Value: Instagram as a discursive party that shapes public opinion on international political issues. This research can be used as a reference for studies on digital political communication, discourse analysis on social media, and the influence of algorithms on public opinion formation.Keywords: critical discourse analyasis (CDA), teun A. van dijk, instagram comments, political ideology, trump and zelensky, public discourse, social media.